2009
DOI: 10.1080/03009740802363768
|View full text |Cite
|
Sign up to set email alerts
|

Sustained improvement of vascular endothelial function during anti‐TNFα treatment in rheumatoid arthritis patients

Abstract: In this small cohort of patients with RA and no clinically overt cardiovascular disease (CVD), after 18 months of treatment with anti-TNFalpha agents, endothelial function improved significantly while CCA-IMT remained stable. Longitudinal studies using more patients are needed to determine the clinical significance of these findings in relation to the risk of atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
0
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 14 publications
7
43
0
5
Order By: Relevance
“…Several studies have demonstrated improved aortic stiffness in patients with inflammatory arthropathies treated by TNF-α antagonists, [171][172][173][174] whereas carotid intima-media thickness was either reduced 174 or remained stable. 175 In contrast, arterial stiffness, lipid profiles, and other traditional cardiovascular risk factors were not improved after 6 and 12 months of anti-TNF-α therapy in patients with ankylosing spondylitis, although the treatment decreased their disease activity. 176 Regarding endothelial function, flow-mediated dilatation in patients with inflammatory arthropathies is strongly impaired when compared with healthy controls.…”
Section: Tnf-α Antagonism In Autoimmune Diseasesmentioning
confidence: 91%
See 1 more Smart Citation
“…Several studies have demonstrated improved aortic stiffness in patients with inflammatory arthropathies treated by TNF-α antagonists, [171][172][173][174] whereas carotid intima-media thickness was either reduced 174 or remained stable. 175 In contrast, arterial stiffness, lipid profiles, and other traditional cardiovascular risk factors were not improved after 6 and 12 months of anti-TNF-α therapy in patients with ankylosing spondylitis, although the treatment decreased their disease activity. 176 Regarding endothelial function, flow-mediated dilatation in patients with inflammatory arthropathies is strongly impaired when compared with healthy controls.…”
Section: Tnf-α Antagonism In Autoimmune Diseasesmentioning
confidence: 91%
“…177,178 Anti-TNF-α treatment was shown to significantly improve endothelium-dependent vasodilation in patients with rheumatoid arthritis. 175,179,180 Other studies in rheumatoid arthritis patients showed a significant but transient effect of infliximab infusion on endothelium-dependent vasodilatation, which returned to baseline within 2-4 weeks post-infusion. 177,181 Beneficial effects on capillary recruitment and endotheliumdependent vasodilatation were also reported in ankylosing spondylitis patients treated either with etanercept, 178 or with infliximab, which was furthermore shown to reduce nitrite concentrations.…”
Section: Tnf-α Antagonism In Autoimmune Diseasesmentioning
confidence: 95%
“…Sidiropoulus и соавт. [90] сообщили об улучшении показателей эндотелиальной функции в течение 18 мес лечения ингибиторами ФНОα.…”
Section: с о в P E м е н н а я р е в м а т о л о г и я № 4 ' 1 2 о б unclassified
“…По данным нашего исследования, в котором изучали влияние ИНФ на субклинические показатели атеросклеро-за у пациентов с РА в течение 12 мес наблюдения, на фоне снижения активности заболевания наблюдалось отсутствие изменений ПЗВД и толщины КИМ, что совпадает с резуль-татами других авторов [90] (см. табл.…”
Section: с о в P E м е н н а я р е в м а т о л о г и я № 4 ' 1 2 о б unclassified
See 1 more Smart Citation